Abordagens para avaliação de software educativo e sua coerência com os modelos de qualidade de software - Brito Junior, Ozonias de Oliveira (2016)
Evaluation of Educational Software (ES) is important to identify the correct use of this tool as a facilitator of the teaching-learning process and also allows you to check the adequacy of the ES in accordance with the educational goals set by teachers; IF the correct operation according to the Software Engineering; the direction to the characteristics, needs and skills of its members, according to Engineering Usability. Therefore, the aim of this study was the analysis of 14 ES approaches to assessment in order to identify the coherence and comprehensiveness in relation to established models of classical literature for Software Quality (ISO 9126-1 and SWEBOK guide), Quality of Service (ISO 9241-1 and Heuristics Usability) and the. Precepts of Education. The process of knowledge appropriation of the approaches, was marked in the study of characterization of the same, from which it was possible to identify great heterogeneity of the adopted criteria, measurement instruments and diagnoses obtained. Thus, there was a comparison between the quality model in order to identify the intersection criteria for different models. As a result of the characterization of the 14 analyzed approaches and the intersection of the Software Quality Models, Use and Teaching, elaborated a dictionary of terms to map the criteria of each quality model, with those present in the ES assessment approaches considered in this study. It is expected that this tool will be useful to assist the actors involved in the ES evaluation process as it uses information taken and understood as a reference standard in the literature.